أثر استقلالية البنك المركزي في رسم وتنفيذ أهداف السياسة النقدية في الجزائر للفترة (1990-2018) - بغداوي، جميلة; حضري، دليلة; عميش، عائشة (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2021)
تهدف هذه الدراسة إلى الوقوف على الأثر الذي تتركه استقلالية البنك المركزي (باعتبارها متغير مستقل) في بعض أهداف السياسة النقدية في الجزائر والمتمثلة في: التضخم، البطالة، وميزان المدفوعات بوصفها متغيرات تابعة تتأثر به، وللوصول إلى الهدف المطلوب استخدمنا المنهج الاستنباطي بأداتيه الوصف والتحليل في الجانب النظري والمنهج الاستقرائي في الجانب التطبيقي، وذلك من خلال مناقشة النقاط التالية: الإطار المفاهيمي لاستقلالية البنوك المركزية، أهداف السياسة النقدية وعلاقتها باستقلالية البنوك المركزية، التحليل الوصفي للمؤشرات الاقتصادية في الجزائر، التحليل القياسي لأثر استقلالية بنك الجزائر على بعض أهداف السياسة النقدية، وقد تم استعمال أسلوب تحليل الانحدار البسيط للوصول للنتائج المطلوبة، وقد خلصت الدراسة إلى جملة من النتائج أهمها: وجود علاقة ارتباطية سالبة بين استقلالية بنك الجزائر وكل من معدلي التضخم والبطالة
This study highlights the impact of the central bank's independence (as an independent variable) on some Algeria's monetary policy: inflation, unemployment, and balance of payments as dependent variables affected by it. To reach the desired target we used both the curriculum Inference with tools of description and analysis in the theoretical and inductive aspect, by discussing the following points: the conceptual framework of the central bank’s independence, the monetary policy objectives and its relationship to the central bank’s independence, descriptive Economic indicators analysis in Algeria, the standard analysis impact of the Algerian Bank’s independence on some monetary policy objectives, and the analysis method of the simple regression was used to reach the required results. The study concluded with a number of conclusions, the most important is a negative correlation between the independence of the Algerian Bank and both the inflation and unemployment rates
Keywords: الجزائر -- الاقتصاد الصرفي -- السياسات الاقتصادية -- النفقات الحكومية